Pelatihan Keterampilan Wirausaha Sablon Manual di Desa Siser, Kecamatan Laren, Lamongan - Arifin, Miftakhul; Maknunah, Jauharotul; Rosady, Siti Duratun Nasiqiati; Novitasari, Eli (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Screen printing is a screen printing technique using textile paint as the base material. In general, they can be divided into two types in their work, some are manual and also use machines/digital. Empowerment of youth youth groups as members of the community and still classified as productive workforce is very important, aiming to foster awareness and independence in doing business, as well as expanding employment opportunities in order to increase family income in an effort to achieve a happy and prosperous family. The purpose of manual screen printing entrepreneurship training activities is to provide knowledge and training on manual screen printing as well as to help create creative industries so that they can create new business opportunities. The training is given in the form of theory followed by direct practice and questions and answers. Practice how to make screen printing printed films and training on the screen printing process. Youth youths are guided by trainers/instructors from the initial stage to completion and then practice making the product themselves.